(untitled) (Groundings Undergraduate, 2016)
Why do females who identify as heterosexual write and/or read male/male erotic fiction? The goal of this paper shall be to highlight one explanation of the appeal this genre holds as a form of entertainment for some, while certainly not all, of its female readers and writers. It will be argued that the key to understanding the genre’s appeal for these women is not the homosexual content of the narratives. Rather, male/male erotic fiction, with its challenge to binary and hierarchical gender roles, is used by them to dabble in privileges traditionally reserved for men and thus as a tool to create quasi-egalitarian experiences for them within a gendered society.